2019
DOI: 10.2147/cmar.s205052
|View full text |Cite
|
Sign up to set email alerts
|

<p>New serum biomarker identification and analysis by mass spectrometry in cervical precancerous lesion and acute cervicitis in South China</p>

Abstract: Background: According to the statistics of WHO/IARC, cervical cancer (CC) has become the fourth malignant cancer of female worldwide and it is one of the main causes of death of women in developing countries. Purpose: Potential plasma and metabolic biomarkers for CC precancerous lesions and cervicitis were indicated by LC-MS techniques, and their underlying mechanisms and functions were analyzed. Methods: Plasma samples were selected from healthy peopl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…HR-HPV is a potent human carcinogen, and persistent HR-HPV infection is a necessary risk factor for the cervix and cervical cancer [ 24 ]. It induces epithelial cell malignant transformation and suppresses the immune response by encoding oncoproteins [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…HR-HPV is a potent human carcinogen, and persistent HR-HPV infection is a necessary risk factor for the cervix and cervical cancer [ 24 ]. It induces epithelial cell malignant transformation and suppresses the immune response by encoding oncoproteins [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…This result suggested LysoPC and PC may also correlate with HR-HPV-induced oncogenesis, consistent with a previous study concluding PC and LysoPC were potential biomarkers for cervical cancer [ 49 ]. LysoPC originates from the cleavage of PC, the main component of oxidatively damaged low-density lipoprotein, was reported to aggregate inflammation and associated with the invasion, metastasis, and prognosis of tumors [ 24 ]. In addition, emerging evidence has indicated that enzymes participating in key lipid metabolism are potential therapeutic targets because they either inhibit lipid synthesis or stimulate their degradation [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Annotation of metabolites was conducted by matching samples with the Kyoto Encyclopedia of Genes and Genomes (KEGG) database and the Human Metabolome Database (HMDB). Data sets were analyzed using principal component analysis (PCA; Ramadan et al, 2006) and the VIP obtained by partial least squares discriminant analysis (PLS‐DA; Souza et al, 2012) was used to analyze the expression of the metabolites (filter condition VIP ≥ 1.0) using MetaboAnalyst 4.0 (Qiu et al, 2019). Preliminary screening criteria were as follows: fold change (FC) >2 times or <0.5, P < 0.05 and VIP value ≥1.…”
Section: Methodsmentioning
confidence: 99%
“…Penaresidin A (1) was identified as a promising biomarker for cervical cancer, which is one of the main causes of death for women in developing countries. 7 To determine the relative stereochemistry of the (2S,3R,4S) protein kinase inhibitor 6 in vitro cytotoxicity against human and murine cell lines 11 :…”
Section: Biological Activity Of Penaresidin a Penaresidin B And Penaz...mentioning
confidence: 99%